Entrepreneurial Resilience and Self Efficacy During the Covid-19 - Mediany Kriseka Putri; Ramadhan Putra Lesmana (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
Throughout Indonesia, MSMEs reflect a national workforce of 97%, so this achievement makes MSMEs the pillars of the Indonesian state economy. The covid-19 pandemic is a major disaster for micro, small, and medium enterprises because it has resulted in a decline in the economic sector. Not only large companies that the covid-19 pandemic has impacted but also micro, small, and medium enterprises (MSMEs) have also experienced the impact. MSME actors must be able to keep up with changes in their business processes by digitizing. This study aims to determine the resilience of business entrepreneurs, namely the Modification of processes and products and business models—functional areas found in business environments such as HRM, Finance, and Marketing. Technology adaption is using technology to make sales reach a broader market. Other sources of business continuation and development will be carried out in the short and long term. This research uses a qualitative method with descriptive data presentation. It uses multiple cases to compare the similarities and differences in business resilience of the three businesses in the culinary sector in Bekasi City. The data sources in this study used interviews with the owners of Rumah Cinta Kue Cinta, Dapur Kyja, and MamdiBekasi.The analysis in this study uses the help of Nvivo software to help analyze interview documents with visualization results that are easy to understand. The results of this study can be concluded that the three business actors carried out various aspects to survive during the co-19 pandemic